2020
DOI: 10.1097/nnr.0000000000000403
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Health Technology for Pediatric Symptom Monitoring

Abstract: Background Pediatric blood and marrow transplant (PBMT) patients experience significant symptom distress. Mobile health (mHealth) technologies can be leveraged to improve understanding of the patient’s symptom experience by providing continuous, real-time, in situ, patient-generated symptom data. This rich data stream can subsequently enhance symptom management strategies. However, limited research has been conducted in this area. Objectives This pilot … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“… 18 The TRU‐PBMT intervention is currently being studied for feasibility, acceptability, and usability. 23 , 24 Thus, the development of mHealth interventions for the pediatric transplant population is in its early stages.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“… 18 The TRU‐PBMT intervention is currently being studied for feasibility, acceptability, and usability. 23 , 24 Thus, the development of mHealth interventions for the pediatric transplant population is in its early stages.…”
Section: Resultsmentioning
confidence: 99%
“… 32 Other studies have reported similar findings. 14 , 24 , 33 Patients may, thus, be willing to use telehealth monitoring and interventions post‐transplant, but persistence in using such apps/devices or interventions, beyond the initial novelty, has yet to be established.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations